Bounded pluralism politics and participation in health policymaking - Leviste, Enrique Niño P. (Philippine Sociological Review, 2004)
This article describes the dynamics of politics and participation in a Philippine locality by examining how the health policy process works in the context of decentralization. Data from key informant interviews and observations of actual health policymaking and implementation activities show that the rise of new venues of power in a locality, such as the professional, educational, socio-civic or cultural, and religious sectors, will not necessarily translate to active private sector involvement in health policy-making. This is primarily due to the nature of everyday politics.